Personal Narratives in Teacher Professional Development: Reflecting on Practices and Growth - Elyakim Nova Supriyedi Patty; Emma Clark; Olivia Davis (International Journal of Educational Narratives, 2026)
Background. The increasing complexity of 21st-century education, driven by rapid technological change, diverse student needs, and continuous policy reform, has exposed significant limitations in conventional teacher professional development models. Many programs remain compliance-oriented and fail to cultivate deep reflective practice, resulting in minimal impact on long-term instructional improvement. This growing gap highlights the urgent need for alternative approaches, with personal narrative-based reflection emerging as a promising strategy to enhance teachers’ self-awareness, pedagogical competence, and professional decision-making. Purpose. This study aims to analyze the role of personal narratives in educational administration in strengthening teacher professional development through reflective practices. Specifically, it seeks to address the limitations of conventional training-based professional development models by proposing a narrative-based reflective framework that fosters deeper engagement, professional identity development, and sustained pedagogical transformation. Method. The research employs a qualitative approach using literature review and descriptive analysis of relevant academic journals, educational literature, and teacher development policies. Results. The findings indicate that the use of personal narratives in reflective practice significantly improves teachers’ ability to evaluate their teaching experiences, identify weaknesses, and design more effective instructional improvement strategies. The discussion reveals that narrative-based reflection functions not only as a self-evaluation tool but also as a transformative mechanism that supports continuous professional growth in educational practice. Conclusion. The study concludes that the integration of personal narratives into educational administration plays a strategic role in enhancing teacher professional development through structured and continuous reflective practices.